Sun Protecting Factor Fortitude Determination of extract of Matricaria chamomilla L. by dint of UV-Visible Spectrophotometry - Dr. Swati Deshmukh; Smita Choudhari; Mahima Ratadiya; Mrs. Varsh Dhulasawant; Dr. Smita Sadar; Dr. Ashish Chimbalkar; Dr. Pallavi Chaudhri; Dr. Aniket Garud (The Bioscan, 2025)
Due to high levels of pollution and depletion in ozone layer sun rays are directly hitting the human skin. There should be trustworthy molecules which will give protection to skin without affecting the normal behavior. The major dictum of research project is to determine SPF (Sun protecting factor) of herbal drug Matricaria chamomilla L. from family Asteraceae, which is previously used in cosmetics. SPF is a laboratory measure of effectiveness of sunscreen factor. Higher the SPF value more protection against ultraviolet radiation which causes sun burn disease. SPF determination is the in vitro testing of sunscreen activity with the help of UV spectrophotometer (290-320). Here different concentrations of Matricaria chamomilla extract were taken under consideration of photo protective test to prove its efficiency in the sunscreen activity. Extract was found to be effective in protecting the sunburn effect through higher SPF. Further study is needed to develop the novel formulation and dose determination.